Reconstruction of Vagina in Cases of Vaginal Agenesis With Normal Uterus - I. N. Tiwari; H. P. Seth; R. Narayanan; P. N. Nayak (Indian Journal of Plastic Surgery)
3 young women have been successfully operated by a modified Mc. Indoe technique of vaginoplasty. The result has been satisfactory from the poiont of view mestruation and sexual intercourse. It remains to be seen, whether they conceive in due course of time.